A visit to motivated classroom - D'Arcangelo, Marcia; WurzBurg, Gerardini; Sheets, Dana; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2003)
This visit takes you inside Marilyn Garber's 11th grade precalculus class in Fairfax County, Virginia, where its clearly identified what students are expected to learn and provides multiple opportunities for them to interact with the content, use knowledge on instructiona strategies in setting objectives, providing feedback, uses strategies of nonlinguistic representations and interact with students on a professional
Title from title screen
Editor, Melanie Maholick ; camera, Gari Griffin ; sound, Robert Silverthorne ; lighting, Eric Martin
Keywords: Motivation in education; Classroom management; Effective teaching; Academic achievement